The Effects of Resistance Training on Bone Mineral Density in Postmenopausal Women – A Review of Current Evidence - Alicja Tabian (Journal of Education, Health and Sport)
Introduction and objective: Osteoporosis is a major public health problem among postmenopausal women, which is featured with decreased bone mineral density (BMD) and high fracture risk. The objectives of the present review is to address the impact of resistance exercise on BMD in postmenopausal women and to evaluate the potential mechanotransduction pathways needed for osteoporosis prevention.